Extracellular Proton Concentrations Impacts LN229 Glioblastoma Tumor Cell Fate via Differential Modulation of Surface Lipids - John, Sebastian; Sivakumar, K. C.; Mishra, Rashmi (Frontiers in Oncology, 2017)
Background: Glioblastoma multiforme (GBM) is a highly aggressive form of brain cancer with marginal survival rates. GBM extracellular acidosis can profoundly impact its cell fate heterogeneities and progression. However, the molecules and mechanisms that enable GBM tumor cells acid adaptation and consequent cell-fate competencies are weakly understood. Since extracellular proton concentrations (pHe) directly intercept the tumor cell plasma membrane, surface lipids must play a crucial role in pHe dependent tumor cell-fate dynamics. Hence, a more detailed insight into the finely-tuned pH dependent modulation of surface lipids is required to generate strategies that can inhibit or surpass tumor cell acid adaptation, thereby forcing the eradication of heterogeneous oncogenic niches, without affecting the normal cells. Results: By using image based single cell analysis and physicochemical techniques, we made a small scale survey of the effects of pH ranges (physiological: pHe 7.4, low: 6.2 and very low: 3.4) on LN229 glioblastoma cell line surface remodelling and analyzed the consequent cell fate heterogeneities with relevant molecular targets and behavioural assays. Through this basic study, we uncovered that the extracellular proton concentration 1) modulates surface cholesterol-driven cell-fate dynamics and 2) induces 'differential clustering' of surface resident GM3 glycosphingolipid which together co-ordinates the proliferation, migration, survival and death reprogramming via distinct effects on the tumor cell biomechanical homeostasis. A novel synergy of anti-GM3 antibody and cyclophilin A inhibitor was found to mimic the very low pHe mediated GM3 supra-clustered conformation that elevated the surface rigidity and mechano-remodelled the tumor cell into a differentiated phenotype which eventually succumbed to the anoikis type of cell death, thereby eradicating the tumorigenic niches. Conclusions and Significance: This work presents an initial insight into the physicochemical capacities of extracellular protons in the generation of glioblastoma tumor cell heterogeneities and cell death via the crucial interplay of surface lipids and their conformational changes. Hence, monitoring of proton-cholesterol-GM3 correlations in vivo through diagnostic imaging and in vitro in clinical samples may assist better tumor staging and prognosis. The emerged insights have further led to the translation of a 'pH-dependent mechanisms of oncogenesis control' into the surface targeted anti-GBM therapeutics.